MENUAI KEBERHASILAN KEPEMIMPINAN PENDIDIKAN PERSPEKTIF KECERDASAN SPIRITUAL (SQ) - Arta Jaya, I Kadek (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The success and failure of educational leadership is determined by the nature and leadership style of the educational institution. To achieve educational leadership success spiritual intelligence is needed. spiritual intelligence and educational leadership are integrated into the framework of achieving of achieving educational success not only in the realm of intelligence, but also success in the spiritual realm. In the specific context spiritual intelligence is intelligence to deal with and solve problems of meaning and value in life, and place behaviour in a broader and richer contect. People who have high spiritual intelligence are indicated by high contemplation abilities, namely having the ability to get inspiration from various things, the ability to convey values and meanings to others, observing various things to attract wisdom or get inspiration, have high creativity and innovation abilities that inspire inspiration. Leaders who have spiritual intelligence will be able to influence their subordinates according to nature and swadharma humanity regadless of race, ethnicity or religion. In the end, it will be able to form a constructive organizational order to achieve accelerative and effective educational goals.